Сечение ηN взаимодействия в области резонанса S11N* (1535) - Дудкин Г. Н. Геннадий Николаевич; Епонешников В. Н.; Кречетов Ю. Ф. Юрий Фёдорович; Трясучев В. А. Владимир Андреевич (1975, 1975)
Заглавие с титульного листа